Overcoming Zinc Oxide Interface Instability with a Methylammonium‐Free Perovskite for High‐Performance Solar Cells - Schutt, Kelly; Nayak, Pabitra K.; Ramadan, Alexandra J.; Wenger, Bernard; Lin, Yen‐Hung; Snaith, Henry J. (Advanced functional materials, 2019)
Perovskite solar cells have achieved the highest power conversion efficiencies on metal oxide n‐type layers, including SnO2 and TiO2. Despite ZnO having superior optoelectronic properties to these metal oxides, such as improved transmittance, higher conductivity, and closer conduction band alignment to methylammonium (MA)PbI3, ZnO is largely overlooked due to a chemical instability when in contact with metal halide perovskites, which leads to rapid decomposition of the perovskite. While surface passivation techniques have somewhat mitigated this instability, investigations as to whether all metal halide perovskites exhibit this instability with ZnO are yet to be undertaken. Experimental methods to elucidate the degradation mechanisms at ZnO–MAPbI3 interfaces are developed. By substituting MA with formamidinium (FA) and cesium (Cs), the stability of the perovskite–ZnO interface is greatly enhanced and it is found that stability compares favorably with SnO2‐based devices after high‐intensity UV irradiation and 85 °C thermal stressing. For devices comprising FA‐ and Cs‐based metal halide perovskite absorber layers on ZnO, a 21.1% scanned power conversion efficiency and 18% steady‐state power output are achieved. This work demonstrates that ZnO appears to be as feasible an n‐type charge extraction layer as SnO2, with many foreseeable advantages, provided that MA cations are avoided. Perovskite solar cells with ZnO exhibit greatly improved stability when the methylammonium cation is excluded. The interfacial acid‐base reactions between methylammonium and ZnO are probed and the degradation kinetics are modulated by the acidity of the organic cation. Solar cells on ZnO films provide improved open circuit voltage, lower series resistance, and lower processing temperatures than those on SnO2.